2016
DOI: 10.1371/journal.pone.0149591
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Comparative Study of Chemosensory Genes Related to Host Selection by Legs Transcriptome Analysis in the Tea Geometrid Ectropis obliqua

Abstract: Host selection by female moths is fundamental to the survival of their larvae. Detecting and perceiving the non-volatile chemicals of the plant surface involved in gustatory detection determine the host preference. In many lepidopteran species, tarsal chemosensilla are sensitive to non-volatile chemicals and responsible for taste detection. The tea geometrid Ectropis obliqua is one devastating chewing pest selectively feeding on limited plants, requiring the specialized sensors to forage certain host for ovipo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 75 publications
3
31
0
Order By: Relevance
“…The GO assignment results of classification of predicted functions in M. Separata were consistent with that of other invertebrates13141516171819. As regard to the number of the identified sensory genes, there was no statistical difference among M. Separata and other Lepidopteran, Dipteran, and Coleopteran species with identified transcriptome111718.…”
Section: Discussionsupporting
confidence: 73%
“…The GO assignment results of classification of predicted functions in M. Separata were consistent with that of other invertebrates13141516171819. As regard to the number of the identified sensory genes, there was no statistical difference among M. Separata and other Lepidopteran, Dipteran, and Coleopteran species with identified transcriptome111718.…”
Section: Discussionsupporting
confidence: 73%
“…However, the legs that also have a special olfaction sense though less sensitive than olfaction in the antennae [33, 34], its olfactory gene database seems incomplete for the L . sticticalis .…”
Section: Introductionmentioning
confidence: 99%
“…SNMPs have been detected in the olfactory sensilla of moths (Rogers et al, 1997;Rogers, Krieger et al, 2001;Rogers, Steinbrecht et al, 2001) and were subsequently shown to be involved in sex pheromone detection in Drosophila (Benton et al, 2007;Jin et al, 2008;Li et al, 2014); their homologues have thus been extensively identified across lepidopteran species. However, the full-length sequences of these EoblSNMPs were not available online; in addition, other chemosensory genes in E. obliqua identified by Ma et al (2016), such as OBPs and CSPs, were confused with genes of its closely related species Ectropis grisescens . However, the full-length sequences of these EoblSNMPs were not available online; in addition, other chemosensory genes in E. obliqua identified by Ma et al (2016), such as OBPs and CSPs, were confused with genes of its closely related species Ectropis grisescens .…”
Section: Discussionmentioning
confidence: 99%
“…The reference genes Eoblβ-actin (Ma et al, 2016) and EoblGAPDH (Sun, Mao et al, 2017) were previously demonstrated to be suitable for estimating relative expression levels of E. obliqua olfactory genes; therefore, we selected them as housekeeping genes to normalize EoblSNMP1-2 gene expression and to correct for sample-to-sample variation. Negative controls were nontemplate reactions (sterilized H 2 O instead of cDNA).…”
Section: Insect and Tissue Collectionmentioning
confidence: 99%